KAJIAN HUKUM ONLINE DISPUTE RESOLUTION (ODR) DI INDONESIA BERDASARKAN UNDANG-UNDANG NOMOR 30 TAHUN 1999 - M Ali Mansyur; Hutrin Kamil (UNISSULA, 2014)
Alternative dispute resolution (ADR) is an out of court dispute resolution. that the parties to the dispute by mutual agreement freely choose the form and procedures contained in the alternative dispute resolution and will be applied in the dispute resolution. One of the breakthrough by using a model of online arbitration, which is known as Online Dispute Resolution (ODR), so that the disputing parties can resolve anywhere he is. This research uses normative juridical approach, an approach to positive law or regulations reserved. By analyzing and evaluating legislation. Online dispute resolution process consists of: The parties agreed in the form of an agreement to resolve the dispute through arbitration online. Although legally, Online Dispute Resolution is not expressly provided in the Act No. 30 of 1999, does not mean there can be applicable in Indonesia. But the arbitrators and judges can use the method of the invention to overcome this law.